Effects of hCG administration on accessory corpus luteum formation and progesterone production in estrous-induced nulliparous Santa Inês ewes - da Fonseca, Jeferson Ferreira; Castro, Ana Carolina Rosa; Arashiro, Eduardo Kenji Nunes; Oliveira, Maria Emilia Franco [UNESP]; Zambrini, Fabiana Nunes; Esteves, Luciana Vieira; Brandão, Felipe Zandonadi; Souza-Fabjan, Joanna Maia Gonçalves (Colegio Brasileiro de Reproducao Animal - CBRA, 2018)
The effect of hCG administration on accessory corpus luteum (ACL) formation, CL area, and plasma progesterone (P4) concentration (ng/mL) seven days after breeding was studied in nulliparous Santa Inês sheep. Intravaginal 60 mg MAP sponges were inserted into ewes for six days and 300 IU eCG i.m. and 30 μg d-cloprostenol latero-vulvar were administered 24 h before sponge removal. Ewes were naturally bred and, seven days after first mating (Day 0; D0), were treated with either 250 IU hCG (hCG group; n = 7) or 1 mL saline solution (control group; n = 7). Blood was collected to determine plasma P4 concentrations and sonograms were performed on Days 7, 10, 13, 16, 19, and 22. Number of CL on D7 was similar (P > 0.05) between hCG (1.3 ± 0.5) and control (1.3 ± 0.5) groups; however, on D13, it was greater (P < 0.05) in the hCG group (2.3 ± 0.5) than in the control group (1.3 ± 0.5). A greater (P < 0.05) luteal tissue area was detected in hCG-treated ewes (n = 4) on Days 16 to 22 than in the animals in the control group (n = 7). Plasma P4 concentration on D13 to D22 was higher (P < 0.05) in hCG-treated animals than in control ewes. Administration of hCG seven days after estrus onset efficiently induced accessory CL formation in ewes, increasing luteal tissue area and plasma P4 concentration.
Keywords: CL; Luteotropic effect; Ovulation induction; Progesterone; Sheep; Ultrasound